2012
DOI: 10.1177/1358863x11431106
|View full text |Cite
|
Sign up to set email alerts
|

Progression of asymptomatic peripheral artery disease over 1 year

Abstract: The pathophysiology and time course of an individual converting from asymptomatic peripheral artery disease (PAD) to symptomatic claudication is unclear. The objectives of this study were: (1) to characterize the extent of atherosclerotic disease in individuals with an abnormal ankle-brachial index (ABI), but without claudication; and over 1 year of follow-up to (2) evaluate the progression of PAD using ultrasound imaging, (3) determine changes in the ABI and leg pain symptoms, and (4) correlate PAD progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…Most individuals detected in population studies with an ABI ≤ 0.90 are asymptomatic, and in some studies only between 10% and 20% of them exhibited IC . However, a significant number of people with asymptomatic PAD show progression over one . None of this rules out the possibility that in populations exclusively of claudicants, most patients present an ABI of 0.90 to 0.50 (75% of our sample), and that, as in other series, the mean value is 0.60 .…”
Section: Discussioncontrasting
confidence: 45%
“…Most individuals detected in population studies with an ABI ≤ 0.90 are asymptomatic, and in some studies only between 10% and 20% of them exhibited IC . However, a significant number of people with asymptomatic PAD show progression over one . None of this rules out the possibility that in populations exclusively of claudicants, most patients present an ABI of 0.90 to 0.50 (75% of our sample), and that, as in other series, the mean value is 0.60 .…”
Section: Discussioncontrasting
confidence: 45%
“…Doppler US is the only noninvasive technique that does not require contrast enhancement, preparation of the patient before the study, or radiation exposure [1,2]. Doppler US is a good method for screening and follow-up, as well as for the definitive diagnosis of peripheral arterial disease [3-7]. Color Doppler US can easily identify arteries by finding round objects with regular pulsation and can be used to detect stenotic or occluded segments [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have examined associations of the ABI with functional status, the majority of these studies have been in participants with existing PAD 1619,21,22 , have had small sample sizes 16,17,19,22 , were cross-sectional study designs 1618,20,21,24,25 , or were not population-based 1619,21,22 . In the current study, we showed that a lower baseline ABI predicts decline in functional status over 11 years in a multi-ethnic cohort of men and women.…”
Section: Discussionmentioning
confidence: 99%
“…The ABI was also significantly correlated with the SF-36 Physical Component Score 16,17 . Two longitudinal studies have also found the ABI associated with functional decline among those with known, prevalent PAD 22,23 .…”
Section: Introductionmentioning
confidence: 98%